A mathematical multi-dimensional mechanism to improve process migration efficiency in peer-to-peer computing environments. Issue 1 (1st January 2018) - Mousavi Khaneghah, Ehsan; Noorabad Ghahroodi, Reyhaneh; Reyhani ShowkatAbad, Amirhosein
Abstract: In high-performance computing systems, choosing a suitable mechanism for migrating the processes has direct effects on the performance of the system. In traditional systems like clusters, process transmission in process migration management is done using a single mechanism. By changing the requirements of computing systems, open systems like grid and peer-to-peer systems are created. In these systems, the system management does not have a complete view of the nature of all processes due to scalability. Therefore, using a fixed mechanism may decrease the performance of the system. This paper represents a mathematical model for choice process migration mechanism using vector definition of global activities and migration mechanisms. This model helps in the management of process migration by considering the system's situation and also based on processes types begin to choose a process migration strategy. The result of evaluation indicates the validity of this mathematical model. The required information for this modeling can be extracted from the data structures of the operating system.